(untitled) (Altre Modernità, 2010)
Human and social studies on emotions are diversely interested in the reality emotions signify. Within this field, the discourse analysis approach focuses its attention on the linguistic expression of emotions and cannot thus extend its evaluation on psychological or sociological implications. What is said can be only explored at a linguistic level, also from a rhetorical perspective that looks at the effects created by discourse categories and topical construction of emotions. Knowledge of findings in related disciplines will nevertheless facilitate the deciphering of discourse analysis of the mechanisms underlying the subject’s intentions, social interactions or representations. In this paper, great attention will be paid to the notion of the intentional value of emotions and of their cognitive content. This pertains to a kind of knowledge derived from belief rather than a form of knowledge earned through evidence. As a sensitive reaction to sensation, emotion expresses itself in behaviour, but as a form of knowledge, emotion has anyhow a rational value based on social agreement and collective representations. Within a discourse analysis’ perspective, emotions and the knowledge they involve are nevertheless the effect not only of what words signify on an emotional ground, but also of the context, the situation and the speakers’ identities. These factors, the interaction of which can be studied from a rhetorical point of view, are to be considered when the influence on others is the aim of a speech, as happens in political discourse.